2018
DOI: 10.1186/s12909-018-1390-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of response instructions and response format on applicant perceptions of a situational judgement test for medical school selection

Abstract: BackgroundThis study examined the influence of two Situational Judgement Test (SJT) design features (response instructions and response format) on applicant perceptions. Additionally, we investigated demographic subgroup differences in applicant perceptions of an SJT.MethodsMedical school applicants (N = 372) responded to an online survey on applicant perceptions, including a description and two example items of an SJT. Respondents randomly received one of four SJT versions (should do-rating, should do-pick-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 43 publications
(73 reference statements)
0
10
0
Order By: Relevance
“…As presented in the study, SJTs might be useful not just as a selection method (e.g., display of performance) but also as an assessment tool for evaluations (e.g., for training curricula). In future studies, the presentation of the developed SJTs may be varied to detect possible adherence factors such as design features [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As presented in the study, SJTs might be useful not just as a selection method (e.g., display of performance) but also as an assessment tool for evaluations (e.g., for training curricula). In future studies, the presentation of the developed SJTs may be varied to detect possible adherence factors such as design features [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following this were three main parts: (i) demographic information: name, age, gender, study year, name of institution; (ii) SJT of 70 items, 10 items per domain; and (iii) a prevalidated feedback form consisting of 10 questions on a five-point Likert scale (1: strongly disagree to 5: strongly agree) about perceived predicative validity, perceived fairness, face validity, applicant differentiation, study relatedness, chance to perform, ease of cheating, relevance, perceived content validity, and item difficulty. 30 All questions were forced marked for participants to avoid missing data, and option "only allow survey to be taken once" was marked to avoid ballot box stuffing. 31 Only Ayesha Fahim had access to data, which was deidentified prior to analysis.…”
Section: 4mentioning
confidence: 99%
“…Previous research suggests that prospective students with lower socio‐economic and ethnic minority backgrounds more often demonstrate negative perceptions of selection and are less confident in their ability to be successfully admitted 3,11 . These subgroups of applicants are shown to have poorer selection outcomes in general, 12,13 which may be partially explained by poorer motivation due to more negative perceptions 14 …”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only one single‐site study was executed in the field of HPE. This research focused on SJTs and concluded that ethnic minority students and first‐generation university students had other preferences in SJT format compared with their traditional counterparts 14 . Another single‐site study that was conducted at an undergraduate psychology programme included a wide range of selection methods but only focused on gender as a background variable 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation